Impact of the Global Financial Crisis on the Gulf Cooperation Council Countries and Challenges Ahead : An Update - Khamis, May (Departmental Papers; Departmental Paper, 2010)
Departmental papers are usually focused on a specific economic topic, country, or region. They are prepared in a timely way to support the outreach needs of the IMF's area and functional departments.